2017
DOI: 10.1108/ijdrbe-05-2016-0019
|View full text |Cite
|
Sign up to set email alerts
|

The dominant influence of logistics capabilities on integration

Abstract: Purpose Using dynamic capabilities theory, this paper aims to posit logistics capabilities (namely information, demand, supply, cooperation and coordination) when integrated at the supply chain level gives rise to supply chain resilience. The current investigation explores further on the inter-relationship among dominant logistics capabilities and integrated logistics capabilities. Design/methodology/approach To test the proposed hypotheses, data were gathered from 339 supply chain professionals and were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 27 publications
(33 reference statements)
1
23
0
1
Order By: Relevance
“…This finding indicates that supply chain resource reconfiguration (CP2; 48.5%) ranked at the top of the list followed by recovery or restoration plans (CP3; 29.5%) and resource reconfiguration (CP1; 22.1%). Literature has emphasized the importance of these three practices in building up resilience capability, especially during times of disruption (Mandal et al , 2017; Olcott and Oliver, 2014). Japanese firms, for example, are found to be able to bounce back from massive earthquake disruptions because they have adopted good contingency planning practices (Ambulkar et al , 2015).…”
Section: Resultsmentioning
confidence: 99%
“…This finding indicates that supply chain resource reconfiguration (CP2; 48.5%) ranked at the top of the list followed by recovery or restoration plans (CP3; 29.5%) and resource reconfiguration (CP1; 22.1%). Literature has emphasized the importance of these three practices in building up resilience capability, especially during times of disruption (Mandal et al , 2017; Olcott and Oliver, 2014). Japanese firms, for example, are found to be able to bounce back from massive earthquake disruptions because they have adopted good contingency planning practices (Ambulkar et al , 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Environmental product performance (waste) is a criterion considered in half of the papers. Analysis of how to manage the waste after customer use and its relationship to performance and sustainability and resilience management appears in recent papers [93,190].…”
Section: Sustainability Resilience Elements E-s E-en Tblmentioning
confidence: 99%
“…This information must include (among others) density, complexity and criticality of the nodes in the face of disruptive events. 28 12.07% [25,26,[29][30][31][32][33]46,114,125,130,157,160,163,165,168,169,190,202,203,205,[212][213][214][215][216][217] Trust…”
Section: Flexibilitymentioning
confidence: 99%
“…Brusset et al (2017) noted that the increased level of cooperation and integration between enterprises can also improve supply chain resilience. Specifically, Mandal et al (2017) believed that information system integration and logistic systems, information sharing, formal and informal communication, process coordination, and others promote the collaborative response of enterprises in the supply chain to uncertainty. Lam et al (2016) suggested that companies should enhance their supply chain relationship management capabilities and form strategic alliances with upstream and downstream companies to enhance the resilient capability of improving market forecasting and risk assessment capabilities.…”
Section: Antecedent Of Supply Chain Resiliencementioning
confidence: 99%